IMPLEMENTASI SPARQL DENGAN FRAMEWORK JENA FUSEKI UNTUK MELAKUKAN PENCARIAN PENGETAHUAN PADA MODEL ONTOLOGI JALUR KLINIS TATA LAKSANA PERAWATAN PENYAKIT KATARAK - Lalu Mutawalli; Indi Febriana Suhriani; Supardianto Supardianto (Jurnal Informatika dan Rekayasa Elektronik, 2018)
Abstract The prevalence of cataracts in Indonesia is very high, this can affect the quality of life, productivity and social aspects will cause the nation's economy to be in a low-level position. Cataract problems certainly need to be considered more, however, on the other hand, the lack of experts (doctors) is an obstacle especially outside the city. Uneven distribution of experts will complicate the conditions for solving problems. With these conditions, a semantic-based information technology approach is needed regarding the treatment of patients with cataracts. Semantic information can provide knowledge to non-physician health workers, this will certainly facilitate the process of prevention and prevention of cataracts. In this research, knowledge is modeled using the ontology concept. We have built an ontology model that can be used as a guide to the management of cataract disease. To extract the built-in ontology model, simple protocol and RDF Language (SPARQL) are used as query languages. Apache Jena Fuseki is used to simplify the process of evaluating knowledge.